Factors associated with overweight and obesity in preschool children - Amira Kurspahić-Mujčić; Amra Mujčić (Medicinski glasnik, 2020)
Aim: To determine factors associated with overweight/obesity in preschool children. Methods: This cross-sectional study was carried out in paediatric outpatient departments of the Public Institution Primary Health Care Centre of Canton Sarajevo, Bosnia and Herzegovina. The study included 300 preschool children who were divided into two groups: normal weight (n=150) and overweight/obese (n=150). Children were weighed and measured and body mass index was calculated. Data concerning potential childhood overweight/obesity risk factors (sociodemographic characteristics of child and mother, physical activity and sedentary behaviour of the child) were collected using a designed questionnaire filled in by the mothers. Logistic regression analysis was used to estimate the association between potential risk factors and overweight/obesity in preschool children. Results: Male gender of the children (p=0.043) and maternal overweight (p=0.000) were positively associated with child overweight/obesity. Male children were 1.6 times more likely to be overweight/obese than female (95% CI: 1.01-2.53). Children of overweight mothers were 3.34 times more likely to be overweight/ obese than children with mothers of normal weight (95% CI: 1.77-6.28). Physical activity <60 minutes/day) (p=0.014), screen time >180 minutes/day (p=0.020), regular snacking while watching television, using computer/tablet/ mobile phones (p=0.000) were associated with overweight/obesity status of the preschool children. Conclusion: Public health programs that aim to reduce overweight/ obesity in preschool children should mainly help mothers understand the serious risk of childhood obesity and the importance of them creating a healthy lifestyle in childhood.
Keywords: paediatric obesity; screen time; exercise; mothers